Another piece of the puzzle: Abiotic habitat properties of salt-marsh creeks benefit small fishes and crustaceans. (5th October 2021) - Friese, Julia D.S.; Temming, Axel; Dänhardt, Andreas
Abstract: Inundated salt marshes are valued as nekton habitat due to their low predator and high prey abundance. But habitat quality depends also on abiotic properties. We measured hydrological (temperature, oxygen concentration) and hydrodynamic (flow velocity, turbidity, sediment grain size) parameters in four German salt-marsh creeks and compared these with the adjacent tidal flat and subtidal area. Water temperatures in the salt-marsh creeks varied with season, daytime and over the tides. In contrast to deeper subtidal areas, the small water body in the marsh creeks adapted rapidly to air temperatures, resulting in relatively cool water temperatures in winter and relatively warm temperatures in summer. Despite high summer temperatures, the oxygen concentration in the creeks remained year round within the tolerance range of most fishes and crustaceans (above 5 mg/L), probably due to tidal mixing and primary production. Furthermore, the water body in the salt-marsh creeks was sheltered by the vegetated marsh surface from wind and waves and thus characterized by low flow velocities (0.15 ms −1 ), as well as lower turbidity and finer sediments than in the subtidal. As the specific set of habitat characteristics in the marsh creeks could explain utilization of this habitat by nekton, we performed a constrained redundancy analysis including temperature and turbidity as explanatory variables. Turbidity explained almost 21% of the variation in nekton species occurrence, while temperature accounted for only 2% of the variation. Compared to larger animals, small-sized nekton, which dominated the salt-marsh nekton community, is more capable to deal with extreme temperatures and will profit more from reduced currents than larger animals. Despite the limited accessibility for aquatic organism, intertidal salt-marsh creeks appear to provide favourable habitat for small nekton due to increased growth potential during seasonally higher temperatures, reduced swimming effort, and increased prey visibility and availability in the muddy sediments. Graphical abstract: Image 1 Highlights: Marsh creeks represent fish habitat with extreme abiotic conditions. Mainly small species and life stages appeared to cope with these conditions. Hydrodynamic energy is reduced, foraging conditions enhanced. Benefits outweigh perils for small nekton utilizing this habitat type. Creek-subtidal connection relaxes trade-off between feeding and predator avoidance.